2019
DOI: 10.1002/ncp.10439
|View full text |Cite
|
Sign up to set email alerts
|

Factors Impacting on Eating in Pediatric Intestinal‐Transplant Recipients: A Mixed‐Methods Study

Abstract: Background: No empirical data are found examining why eating may be difficult for some children following intestinal transplant and not others. This study aimed to describe the eating behaviours and nutritional intake of intestinal transplant recipient children and examine factors that may impact on their eating. Methods: Caregivers of all (n=34) intestinal transplant recipients <18 years in the United Kingdom were invited to participate in this mixed methods study comprising a quantitative component (question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In our study, all of the transplanted patients except 1, who was <1‐month post‐transplant, achieved enteral autonomy. A recent study suggested that promoting safe oral feeds pre‐transplant is one of the main predictors of successful eating after transplant, which can significantly impact the quality of life of these patients (26). In our study, we observed that among the transplanted patients who achieved enteral autonomy, 8 were on full oral feeds and among the 11 nontransplanted patients, 8 were on at least minimal oral feeds.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, all of the transplanted patients except 1, who was <1‐month post‐transplant, achieved enteral autonomy. A recent study suggested that promoting safe oral feeds pre‐transplant is one of the main predictors of successful eating after transplant, which can significantly impact the quality of life of these patients (26). In our study, we observed that among the transplanted patients who achieved enteral autonomy, 8 were on full oral feeds and among the 11 nontransplanted patients, 8 were on at least minimal oral feeds.…”
Section: Discussionmentioning
confidence: 99%
“…In high volume centres the outcomes for isolated intestinal grafts are similar to the survival on home PN [40,41]. Long-term nutritional autonomy is achievable in the majority of patients, though there can be challenges with regards to eating behaviours and food avoidance, particularly in children [39,42].…”
Section: Cost Effectiveness Outcomes and Quality Of Life Considerationsmentioning
confidence: 99%
“…Progression to an oral diet can be more difficult due to food aversion as food might be associated with negative symptoms. Especially in paediatric patients, who sometimes have never eaten before or in limited amounts, this can pose a challenge, requiring stepwise introduction by an experienced nutritionist [46]. Some centres also avoid lactose and are careful with typical allergens (e.g.…”
Section: Diet In the Rehabilitation Period: Oral Nutritionmentioning
confidence: 99%